(untitled) (American Journal of Islam and Society, 2012)
This article compares and contrasts a western post-Enlightenment theory of knowledge with a Qur’anic epistemology. It first analyzes the development of post-Enlightenment epistemology, which resulted in the disappearance of established meaning and the implanting of doubt. Thereafter, western epistemology began to deal with such questions as “What can I know?” and “How can I distinguish between those things that I am justified in believing over those things that I am not justified in believing?” Eventually, this developed into the two dominant and diverging paths that persist until today: “We might be able to know the truth” (plausibility) or “We are unable to know anything” (denial). What makes this so important is its eventual influence upon the Muslim world with the advent of colonialism, European preeminence, and globalization. That influence, it is argued, has been disastrous because of its ability to uproot the indigenous Islamic epistemic tradition. Therefore this article, by focusing on various Qur’anic verses, shares insights for an alternative epistemology that would begin to rectify this dissonance. It does so by discussing the features of a Qur’anic epistemology, one that begins with the affirmation or certainty of “God knowing” with the potential for “human knowing.” In other words, it establishes an optimistic attitude toward “true” knowledge being possible (viz., “I” may be wrong, although God knows) and the potentiality of certainty being ever-present.